A Second Supplementary Bibliography on Monopolistic Competition - Chamberlin, Edward H. (Quarterly Journal of Economics, 1956)
A Second Supplementary Bibliography on Monopolistic Competition Get access Edward H. Chamberlin Edward H. Chamberlin Harvard University May 1956 Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 70, Issue 4, November 1956, Page 613, https://doi.org/10.2307/1881868 Published: 01 November 1956